Ceramika naczyniowa z zamku w Brześciu Kujawskim na tle specyfiki późnośredniowiecznej i nowożytnej ceramiki kujawskiej - Kapusta, Elżbieta (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
Although the archaeological and architectonic works were carried out in Brześć Kujawski castle from 1989-1992, vessel ceramics from the first season of excavations (2174 fragments) only is the subject of this article. Changes in the picture of the late mediaeval and early modern vessel pottery articles is shown by Brześć assemblage which was the subject of technological anf formal analysis. The basis of the assemblage are sherds fired in the reduced atmosphere (82,06%). Elements characteristic to the end of early mediaeval period outlive there (16,61%). Fragments of vessels fired in advanced oxidizing atmosphere, glazed vessels and the ones covered by painting or slip are the trace part (1,33%). The rythm of changes of technological group corresponds directly with assemblages from Raciążek and Radziejów castles and specifies the northern zone of the late mediaeval and modern Kujawy ceramics. The formal feature of the collection from Brześć, makes it close to the various assemblages from Kujawy, particularly to the one from Franciscan cloister in Inowrocław. During the excavation in 1989, 3 fragments of the so-called hussitic sherds were found. They are dated (by stratification) to the second half of the 16th century and have a local provenance. They have their counterparts to other kind of these founds known from Kujawy region. The collection from Brześć Kujawski dated back from half of the 14th century to the half of the 17th century (which limits the time of the fundation of the castle structure and its abandonment after the Swedish invasion).